Implementation of Education and Training Management (Diklat) for the Development of Teacher Professionalism at SMK Cerdas Murni School - Rustam Rustam (Universitas Negeri Malang, 2025)
Abstract: Teacher professionalism is a critical factor in improving the quality of education, requiring continuous enhancement through structured education and training (diklat) programs. This study aims to explore how the management of education and training is implemented to support teacher professionalism at SMK Cerdas Murni. Employing a descriptive qualitative approach, data were collected through interviews, observation, and documentation from key stakeholders including the school principal and teachers. The results reveal that the planning of training programs is conducted systematically and collaboratively, aligning with teachers’ actual needs identified through supervisory reports and curriculum implementation analysis. Training activities are implemented flexibly with competent facilitators and adopt practical methods such as simulations and project-based learning (P5), fostering both pedagogical and professional competencies. Evaluation is performed multilaterally, incorporating feedback and supervision, which informs continuous program improvement. The study concludes that effective training management—encompassing well-planned, contextually implemented, and continuously evaluated programs—has significantly enhanced teachers' confidence, innovation, and collaboration, positioning diklat not just as an administrative requirement but as a transformative professional and spiritual process. Keywords: Training Management; Teacher Professionalism; Education and Training; Vocational School; Competency Development